Descriptive study of Extragastrointestinal Manifestations of Ulcerative Colitis and their relation to disease activity in 100 Iraqi patients - Al-Khazraji, Khalid A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Ulcerative colitis is a chronic inflammatory bowel disease (IBD); its extragastrointestinal manifestations vary from one country to another. This study identifies the prevalence of the extragastrointestinal manifestations in a sample of Iraqi patients with ulcerative colitis and their relation to disease activity. Patients and Methods: A descriptive study was conducted on 100 patients with established diagnosis of ulcerative colitis, who attended Baghdad Teaching hospital and Gastroenterology center in Baghdad during the period from May 2009 to January 2010. A direct interview and thorough clinical examination were done to determine the history of the disease, its severity and the presence or absence of the extraintestinal manifestations. Result: The Extragastrointestinal manifestations were observed in 17 patients (17%). The most common EGlMs were the peripheral arthritis and mouth ulcer. The EGlMs were more common in patients with severe disease. Conclusion: The EGlMs of ulcerative are less common in Iraqi patients than in patients from western countries, but their relation with disease activity was relatively similar.